Influence Of Machiavellianism, Love of Money, And Religiosity On The Tendency of Fraud Accounting In Luwu Raya: A Quantitative Study With Smart-PLS - Widyananda, Indah; Antong, Antong; Usman, Halim (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the influence of Machiavellianism, love of money, and religiosity on the tendency of accounting fraud among public sector employees in the Luwu Raya area. Methodology: This research employs a quantitative approach with a survey design. Data were collected through purposive sampling using structured questionnaires distributed to public sector employees who met the research criteria. The data were analyzed using Partial Least Squares (PLS) with SmartPLS 4 to test the proposed hypotheses. Results: The results indicate that Machiavellianism has a positive and significant effect on the tendency of accounting fraud, while love of money shows no significant effect. Religiosity is found to have a negative and significant effect on fraud tendency, indicating its role in suppressing unethical behavior. Novelty: This study integrates psychological traits and moral values into a single empirical model to explain accounting fraud tendencies in the public sector context. Findings: Religiosity functions as a moral control mechanism that can reduce fraudulent behavior, while Machiavellian traits increase fraud risk. Originality: The originality of this study lies in its empirical evidence from Indonesian public sector employees, a context that remains underexplored in fraud behavior research. Conclusions: Strengthening ethical character and religious values is essential for fraud prevention in public sector organizations. Type of Paper: Empirical Research Paper.